Politeness Strategy Used by Lecturer in Teaching Process - Tsamratul’aeni Tsamratul’aeni (Institut Agama Islam Negeri Palopo, 2019)
This research aims to find out the politeness strategy that used by lecturer in teaching process in English Class. This research used descriptive qualitative method. The population of this research is the lecturers of English Language Education Study Program. In determining the samples, the researcher used random sampling technique. Total number of sample is 3 lecturers and used observation to collect the data. The result of this study shows: (1) There are four kind of politeness strategies that commonly used by lecturers in teaching process. Such as bald on record, positive politeness, negative politeness and off record (2) The politeness strategy that commonly used by lecturers is positive politeness.